The Influence of the Effectiveness of Icebreaking Implementation on the Learning Motivation of Class II Students at SDN 141 Pekanbaru - Arsita, Sesra; Hadiyanti, Putri Octa (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Icebreaking is an activity that can lighten the mood and create a friendly atmosphere. The purpose of this research is to discuss the effectiveness of icebreaking for class II students. There were 20 students involved in the experimental research design. The instrument used is a questionnaire that has been validated and reliable in data collection. Findings regarding student learning motivation have met the criteria for analysis and hypothesis testing. The research results showed that icebreaking had an impact on increasing the enthusiasm for learning of class II students at SDN 141 Pekanbaru. It can be concluded that the second data variant is homogeneous because the data obtained, for example Ha, is acceptable. Significance level test α = 0.05 with dk = 9; ttable =.012; and tcount = 9 is used in hypothesis testing calculations. Class II students at SDN 141 Pekanbaru have a strong influence on the use of icebreaking because tcount (0.012) > ttable (9). Therefore it can be stated that Ha is accepted and Ho is rejected.